European Court of Human Rights for mandatory vaccination of children ‒ Vavřička and others against Czech Republic (Discourse of Law and Administration, 2022)
The much-awaited judgment of the European Court of Human Rights in the case of Vavřička and others against Czech Republic issued in April 2021 is seen as the voice of international authority in the global and long-lasting debate on the advisability of compulsory vaccination in general, including the vaccination of children. The timing of this ruling and the background controversy surrounding the Covid-19 vaccination, that some states consider compulsory in the future at least for some groups of people (like medical staff, teachers, administration staff) make us to see this judgment in wider dimension. This impression is even intensified by the fact, that in July and November 2021 the Court rejected a few requests for granting interim measures from the French and Greek applicants, medical professionals, on whom France and Greece have imposed mandatory vaccination against Covid-19. Making those decisions the Court again took a stance for mandatory vaccination (this time against Covid-19) at some point. The aims of these consideration are twofold. First, to analyze, to what extend the Court itself marked its judgement in the case of Vavřička and others against Czech Republic with the meaning, that could be used in discussions regarding the possible compulsory vaccinations against Covid-19. Secondly, how the Court’s opinion can be understood or even used in providing and promoting such compulsory vaccination,despite the fact, that the Court has distanced itself and this particular judgment from such effect.
Keywords: human rights; European system of human rights; compulsory vaccination; medical intervention